Retention of Digitally Duplicated Maxillary Denture After Clinical Relining: A Case Report - Jamila Almuhamadi; Rayan Aljama; Malak Nesrat; NajmUdin Nusrat (AlQalam Journal of Medical and Applied Sciences, 2026)
Retention of maxillary complete dentures is critical for prosthetic success and patient comfort. Recent advancements in digital technology, particularly intraoral scanning and 3D printing, have introduced denture duplication as a promising alternative to conventional techniques. However, clinical evidence regarding its impact on denture retention remains limited. To evaluate the retention of a digitally duplicated maxillary complete denture fabricated using intraoral scanning and 3D printing, with particular emphasis on the effect of incorporating a clinical relining step into the digital workflow. This case report describes the digital duplication of an existing maxillary complete denture in a 57-year-old patient. The patient presented with an old denture that was clinically acceptable. Initially, duplication was attempted by scanning both the denture and a dental cast obtained before relining. However, the software failed to achieve accurate alignment between the scans. Consequently, a conventional clinical relining impression was performed before repeating the digital workflow. The digitally duplicated and relined maxillary denture demonstrated satisfactory clinical fit, retention, and adaptation. Incorporating the conventional relining step before scanning improved scan alignment and enhanced the overall accuracy of the digital workflow, resulting in acceptable denture retention. This case demonstrates that integrating conventional clinical relining with digital duplication techniques can overcome current limitations in scan alignment. Digital duplication of maxillary complete dentures using intraoral scanning and 3D printing represents a promising and effective approach to improving denture retention, particularly when combined with established clinical procedures.